Examining the impact of early life adversity on adolescent sleep health: Findings from the ABCD study - Hunt, Ethan T.; Brazendale, Keith; Ferreira De Moraes, Augusto César; Nascimento-Ferreira, Marcus Vinicius; Pfledderer, Christopher D.; Izabel, Sarah Sampaio; Dooley, Erin E.; Chen, Baojiang; Fernandez, Alejandra; Johnson, Micah E.; Garavan, Hugh; Potter, Alexandra S.; et al. (Child protection and practice, 2025)
Sleep irregularity are associated with health outcomes, particularly during adolescence. Early adversity may exacerbate sleep irregularity, but longitudinal evidence remains limited. To investigate the relationship between early adversity, social jetlag, and weekly sleep loss in youth from the Adolescent Brain Cognitive Development (ABCD) Study. The sample included 11,002 adolescents (mean age at 2-year follow-up = 12.03 years, SD = 0.67) from the ABCD Study (53 % boys and 47 % girls). Racial/ethnic composition was 53 % White, 14 % Black, 20 % Hispanic, and 13 % other/multi-racial. Social jetlag and weekly sleep loss were assessed using the Munich Chronotype Questionnaire at 2-year and 3-year follow-ups. Concurrently, lifetime adversity was measured using 16 of 17 items from the Pediatric Early Adversity and Related Life Events Screener (PEARLS). Mixed-effects linear and logistic regression models examined associations between lifetime adversities and sleep, adjusting for key covariates. Adolescents experienced an average of 2.13 ( ± 1.9) hours of weekly sleep loss, and 33.32 % reported four or more PEARLS. Adolescents with four or more PEARLS experienced greater weekly sleep loss (coef. = 0.38, 95 % CI: 0.26, 0.51), translating to 23 min of additional sleep loss per week. Adolescents with four or more PEARLS were also more likely to experience more than 1 h of social jetlag (aOR = 2.79, 95 % CI: 2.19, 3.55). Early adversity is associated with social jetlag and sleep loss in adolescence, suggesting that targeted prevention approaches may improve sleep regularity and quantity. •Adolescent sleep quality is impacted by early adversity, with greater social jetlag and sleep loss linked to childhood adversity.•Sex differences in sleep responses to adversity emerged, with girls showing higher odds of sleep disturbances.•Trauma-informed care is crucial, suggesting mitigating childhood adversity may improve adolescent sleep and development.